SENSIBILIDADE ANTIMICROBIANA DOS STAPHYLOCOCCUS AUREUS ISOLADOS NO LEITE DE VACAS COM MASTITE - Nader, A. [UNESP]; Ferreira, L.m. [UNESP]; Do Amaral, L.a. [UNESP]; Rossi, O.d. [UNESP]; Oliveira, R.p. [UNESP] (Instituto Biológico, 2022)
The purpose of this study was to determine the in-vitro susceptibility pattern of 72 Staphylococcus aureus strains, isolated from bovine mastitic milk. The calves were reared on 10 dairy farms in the state of São Paulo, Brazil. These strains were tested by the standardized disc diffusion method. The highest susceptibility was to gentamicin (98.6%) and erytromycin (98.6%), followed by streptomycin (94.4%), oxacillin (84.7%), novobiocin (73.4%), vancomycin (72.2%), ampicillin (4.2%) and penicillin (2.8%). Results showed that 72 (100%) strains were resistant to at least 2 antibiotics and chemotherapeutics. None of the active principles, acting alone, was effective against any of the strains tested.

Este trabalho teve por objetivo conhecer a sensibilidade antimicrobiana “in vitro” de 72 cepas de Staphylococcus aureus isoladas em amostras de leite de vacas com mastite clínica e subclínica, em 10 propriedades rurais do Estado de São Paulo. Os testes foram realizados pela da técnica de difusão em discos padronizada por Kirby-Bauer. Os principios ativos que apresentaram maior sensibilidade foram a gentamicina (98,6%) e a eritromicina (98,6%), seguidos pela estreptomicina (94,4%), oxacilina (84,7%), novobiocina (73,4%), vancomicina (72,2%), ampicilina (4,2%) e a penicilina (2,8%). Os resultados obtidos evidenciaram, ainda, que as 72 (100%) cepas estudadas apresentaram resistência a pelo menos 2 antibióticos ou quimioterápicos e que nenhum destes princípios ativos, agindo isoladamente, pode ser ativo contra qualquer das cepas experimentadas.
ANTIMICROBIAL SUSCEPTIBILITY OF STAPHYLOCOCCUS AUREUS ISOLATED FROM BOVINE MASTITIC MILK
Keywords: Stahylococcus aureus; bovine mastitis; antimicrobial; Stahylococcus aureus; mastite bovina; antimicrobianos